A study on the feasibility of axillary reverse mapping with blue dye only in breast cancer patients - Shanmugam, Subbiah; Husssain, Syed Afroze; ., Muralikannan (International Surgery Journal, 2019)
Background: Axillary reverse mapping is (ARM) the concept of visualization of the nodes in axilla that drain the arm and preserving them. Literature describes this procedure being done with blue dye (methylene blue) and 99mTC technetium sulphur colloid. This study was undertaken to look for the feasibility of axillary reverse mapping using blue dye alone as there is lack of availability of the radio colloid in many centres in India. Methods: 30 breast cancer patients who underwent axillary dissection as part of their surgery were included in the study. 2.5–5 ml of methylene blue was injected in the medial upper arm in the intermuscular groove region. The number of blue nodes identified, their location, pathological status and procedure related complications were analysed. Results: The ARM blue node was identified only in 7 out of the 30 patients (sensitivity– 23%) and none had a pathologically positive blue node. In those 7 patients, only 1 blue node was identified. All the nodes were in level 1 and the largest node measured 2cm in largest dimension. The complications associated with the procedure included pain, pigmentation, induration and skin necrosis. 16 (53.3%) had pain, 10 (33.3%) had induration, 6 (20%) had pigmentation and 1 (3.33%) had skin necrosis. Conclusions: The feasibility of ARM being done using blue dye alone needs to be questioned in view of its poor sensitivity. Added to this, the complication rates are higher. However, larger studies are needed to validate the same or otherwise.